DEPRECIATION AND INCOME MEASUREMENT. - Devine, Carl Thomas (The Accounting Review, 1944)
Abstract There is something wrong with charging a long-lived asset to expense in the period of its acquisition. To follow this practice in ordinary commercial accounting is, however, no more unreasonable than various retirement proposals that would take no depreciation until the unit is retired. For the accountant the criteria for writing off assets are independent of the initial bricklayers and of the wrecking crew that removes the last debris. What then should be signals for taking depreciable assets to expense? Perhaps the most common argument is that assets should be depreciated as their services are rendered. This approach has been emphasized as an ideal toward which accountants are working and by which their practical measures may be tested, yet this ideal is based mainly on a vague feeling of justice which seems to be in need of independent support. It is the primary purpose of this article to examine once again the income concept and to suggest an alternative for the ethical approach. Many small businessmen do not think they have any profit until the original investment has been entirely recovered, although this type of thinking is contrary to the attitude accountants attempt to instill in their clients, it is sometimes not unreasonable.